Enhancing the Academic Library Experience with Chatbots: An Exploration of Research and Implications for Practice. Issue 3 (3rd July 2019) - Mckie, Indra Ayu Susan; Narayan, Bhuva
ABSTRACT: This paper explores the potential of using chatbots to improve the academic research experience for university students with a literature-based discussion reflecting on a prototype being developed at the University of Technology Sydney (UTS). The paper proposes that information professionals need to adapt emerging technologies such as chatbots to innovate, improve and support library services. Designing a positive experience for the user is essential to ensure that such technological solutions are sustainable. In this exploratory paper, we argue that it is important that librarians engage with the conversational design of the library chatbot in collaboration with the technology developers in order to make it useful, friendly, trustworthy, and customisable for university students.